Applications of an Innovative Strength Parameter Estimation Method of the SoilRock Mixture in Evaluating the Deposit Slope Stability Under Rainfall - Fu, Xiaodong; Zhang, Zhenping; Sheng, Qian; Zhou, Yongqiang; Huang, Juehao; Wu, Zhe; Liu, Mingyang (Frontiers in Earth Science, 2021)
Deposit landslides are one of the most representative geological hazards around the world, and the poor understanding of the mechanical characteristics of the soil-rock mixture (S-RM) inside increases the difficulties for the evaluation of the deposit slope subjected to rainfall. This study attempted to propose an innovative strength parameter estimation method of the soil-rock mixture based on the concept and format of the generalized Hoek-Brown criterion. The system of ‘rock blocks-soil-contact surface’ was considered as the main source to provide resistance to external force and the effect of the contact surface between rock blocks and soil matrix and the components were taken into account. The verification of the estimation method was proved based on abundant test data. A typical deposit slope located in the Taoyuan region of Yunnan province, China was selected as a case study, and the estimation method was applied to provide the shear parameters of the soil-rock mixture inside the slope. The slope stability subjected to different rainfall types was carried out considering the parameter deterioration and the results show that the deposit landslide is more prone to the wave type rainfall, which shows a deeper response depth of pore water pressure and a smaller safety factor. The present study suggests a simple estimation method for the shear parameters of the soil-rock mixture using a few parameters for the engineers and provides an understanding of the deposit slope stability during the rainfall process.